Cognitive image, affective image, cultural dimensions, and conative image: A new conceptual framework - Yang, Shaohua; Isa, Salmi Mohd; Yao, Yiyue; Xia, Jinyuan; Liu, Danping (Frontiers in Psychology, 2022)
Destination image is essential to tourist loyalty and has been heatedly discussed among researchers and marketers in tourism industry for decades. Based on works of literature in this line, the destination image model, including cognitive image, affective image, and conative image, has been firmly established as an acceptable means to gain an understanding of tourists’ behaviours toward revisit and recommendation intentions. The understanding of the moderating role of cultural constructs is still unclear, especially in cross-cultural travel behaviour. Therefore, this conceptual paper proposes an integrated model of cognitive-affective-conative image that includes the constructs of individualism and uncertainty avoidance. Based on the underpinning theories and empirical studies, this paper proposes affective image potentially mediates the correlation between cognitive image and conative image, and this model meanwhile incorporated individualism and uncertainty as a potential moderating effect between affective image and conative image. By integrating individualism and uncertainty avoidance into the theoretical model from tourism perspectives, this paper contributes to a more comprehensive understanding of the influence on travel behaviour on emerging tourism marketing.